Philosophy of Viśiṣṭādvaita Vedānta : a study based on Vedānta Deśika's Adhikaraṇa-sārāvalī - Srinivasa Chari, S. M. (Motilal Banarsidass, 2008)
Study of Adhikaraṇasārāvalī of Veṅkaṭanātha, 1268-1369, work on the fundamentals of Viśiṣṭādvaita philosophy.